Female Offenders Under Community Supervision: A Phenomenological Analysis - Rivas, Michele (Journal of addictions & offender counseling, 2021)
In this phenomenological study, we examined the lived experiences of 10 female offenders under community supervision. Findings include five essential themes. We propose clinical implications and actionable service recommendations for clinical mental health counselors working with this population.